Prospective Randomized Study of MiniArc and Ajust Single Incision Sling Procedures. Issue 3 (27th October 2013) - MARTAN, Alois; KRHUT, Jan; MAŠATA, Jaromír; ŠVABÍK, Kamil; HALAŠKA, Michael; HORČIČKA, Lukáš; ZACHOVAL, Roman
<x xml:space="preserve">Abstract</x> Objectives The aim of this study was to evaluate the efficacy of the Ajust and MiniArc system mini‐sling anti‐incontinence procedures for female stress urinary incontinence, at a minimum of 24 months after surgery. Methods This prospective, randomized, multicenter study included 66 women with previously untreated stress urinary incontinence, and 63 patients completed the study. These women were randomly divided into two groups; the first group of patients underwent operations using the Ajust (n = 33) technique, while the second group were treated with the MiniArc (n = 33) technique. The efficacy of the Ajust and MiniArc procedures (n = 31/32) was evaluated at an average of 28/29 months (minimum24 months) after the procedures. Subjective assessment of the cure rate and the leakage of urine was based on the International Consultation on Incontinence Questionnaire ‐ Short Form (ICIQ‐UI SF) and five‐point Likert scale. Objective assessment of leakage of urine was assessed by the cough test. Results Subjective assessment by the ICIQ‐UI SF questionnaire showed that 93.5–96.9% of patients were dry or improved 28/29 months after the Ajust/MiniArc operations. Based on evaluation by means of the Likert scale, 83.9/81.3% of patients in the Ajust/MiniArc group were dry or improved. Objective assessment by cough test showed that 93.5/81.3% of patients had negative results for this test 28/29 months after the Ajust/MiniArc procedures. Conclusions The cure rates of the Ajust and MiniArc procedures are very good with the follow‐up of 24 months.